2003
DOI: 10.1029/2002jd003019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spatial and temporal variability in soil moisture on widths and δ13C values of eastern Siberian tree rings

Abstract: [1] We studied the relationships between earlywood/latewood width, stable carbon isotope ratio (d 13 C) of cellulose, and soil moisture at a dry and a wet site in Yakutsk, eastern Siberia, which differed considerably in soil water conditions. Recharge of soil water by snowmelt in spring and subsequent drought in summer provided a marked seasonal contrast in soil water conditions between the earlywood and latewood formation period. Ring index was calculated by dividing each earlywood/latewood width by the 5-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 35 publications
6
43
0
Order By: Relevance
“…This is consistent with field gas exchange measurements that showed the piñons at the xeric site exhibited greater changes in water-use efficiency between years relative to the mesic site (Newberry 2008). Similar results have been found in a comparison of d 13 C signal in latewood at a wet site versus a dry site in a study of conifers in Siberia (Kagawa et al 2003) where trees on the wetter site showed less seasonal variation in d 13 C in response to drought relative to the dry sites. Similarly, Adams and Kolb (2004) found a strong d 13 C leaf response to drought in ponderosa pine growing near its lower elevation range limit but not at higher elevations.…”
Section: Discussionsupporting
confidence: 84%
“…This is consistent with field gas exchange measurements that showed the piñons at the xeric site exhibited greater changes in water-use efficiency between years relative to the mesic site (Newberry 2008). Similar results have been found in a comparison of d 13 C signal in latewood at a wet site versus a dry site in a study of conifers in Siberia (Kagawa et al 2003) where trees on the wetter site showed less seasonal variation in d 13 C in response to drought relative to the dry sites. Similarly, Adams and Kolb (2004) found a strong d 13 C leaf response to drought in ponderosa pine growing near its lower elevation range limit but not at higher elevations.…”
Section: Discussionsupporting
confidence: 84%
“…As with most pines, P. sylvestris is an opportunistic species highly responsive to precipitation pulses if water becomes limiting at any moment during growth [58,62]. The prevalence of drought effects over low temperature restrictions on growth suggests that warming-induced water limitation will progressively spread over areas of North Asia-having low precipitation but, also, very low temperatures (i.e., under extreme continentality)-as already observed in Yakutia [56]. Drought effects on Scots pine may not be limited to growth impairment, but they may also hamper the formation of a functional xylem structure via a reduction of cell lumen and wall thickness, as shown for the region [33,63].…”
Section: Drought Rather Than Low Temperatures Determines Long-term Rementioning
confidence: 94%
“…Indeed, the observation that radial growth and ∆ 13 C were tightly (positively) associated at both sites is expected under frequent and intense drought episodes, since both traits are strongly influenced by water shortage in Scots pine [37,56]. P. sylvestris is a conifer with a high stomatal sensitivity to water availability [57].…”
Section: Site Differences In Tree Performance As Indicated By Radial mentioning
confidence: 99%
“…Studies of the isotopic composition of tree rings in the northern regions of Eurasia have been primarily conducted for C (d 13 C) (Kagawa et al 2003;Gagen et al 2007;Kirdyanov et al 2008;Sidorova et al 2008) and rarely for O d 18 O (Saurer et al 2002;Sidorova et al 2008), but using both isotopes could be very helpful in improving our understanding of the forest response to environmental changes of the past century.…”
Section: Introductionmentioning
confidence: 99%